Combined CA125, NSE, and multiple inflammatory indices for diagnosis of oral squamous cell carcinoma - Abudukelimu, Kudelaiti; Tuerxuntayi, Ailifeire; Aierken, Aikepaer; Keranmu, Rexiati; Wufuer, Duolikun (Frontiers in Oncology, 2025)
ObjectiveTo investigate the changes of serum carbohydrate antigen 125 (CA125), neuron-specific enolase (NSE), neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and systemic inflammation response index (SIRI) in patients with oral squamous cell carcinoma(OSCC) and their diagnostic value for OSCC.Subjects and methodsA retrospective analysis was conducted on 136 patients with oral squamous cell carcinoma (OSCC) and 34 healthy controls. Blood routine parameters, as well as serum levels of CA125 and NSE, were obtained for the patients. Additionally, the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic inflammation response index (SIRI) were calculated. The diagnostic value of each marker, both individually and in combination, was evaluated using receiver operating characteristic (ROC) curve analysis.ResultsWe found that the levels of CA125, NSE, NLR, PLR, and SIRI in the oral squamous cell carcinoma group were significantly higher than those in the healthy control group (PCA125<0.001, PNSE=0.004, PNLR=0.034, PPLR=0.035, PSIRI=0.012). Significant differences were observed in NLR, PLR, and SIRI with respect to the size of the primary tumor and local lymph node involvement, as well as substantial differences in NLR and SIRI with distant metastasis (P<0.05). When NLR, PLR, and SIRI were combined with CA125 and NSE, the area under the curve (AUC) significantly increased (P<0.05). Further analysis using Delong’s test revealed a statistically significant difference in AUC values, suggesting that the combined diagnostic approach was more effective than individual markers.ConclusionThe diagnostic efficiency of OSCC can be enhanced by combining CA125, NSE, NLR, PLR, and SIRI. This combined approach offers high sensitivity and specificity for early diagnosis.